2019
DOI: 10.1111/jfb.13955
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between swimming capacities and morphological traits of fish larvae at settlement stage: a study of several coastal Mediterranean species

Abstract: Experimental measurements were made in the laboratory to determine the swimming capacities of settlement‐stage fish larvae of several Mediterranean coastal species collected from the nearshore waters of Corsica, France. Critical swimming speed (Ucrit, cm s−1) was measured to provide a realistic laboratory estimate of in situ swimming speed. Morphometric traits were measured to assess potential predictors of a species’ swimming ability and, when possible, daily otolith increments were used to estimate age. Obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 65 publications
1
13
0
Order By: Relevance
“…However, age (DPH) and size (TL) were the best predictors of swimming performance (critical swimming speed and swimming endurance) for white seabream larvae. In the north-western Mediterranean Sea, several Sparidae larvae, including white seabream larvae, also showed significant relationships between critical swimming speed and body length [31]. However, other studies have found that body length was not the main factor responsible for critical swimming speed variability [30,33].…”
Section: Swimming Performance and Larval Conditionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, age (DPH) and size (TL) were the best predictors of swimming performance (critical swimming speed and swimming endurance) for white seabream larvae. In the north-western Mediterranean Sea, several Sparidae larvae, including white seabream larvae, also showed significant relationships between critical swimming speed and body length [31]. However, other studies have found that body length was not the main factor responsible for critical swimming speed variability [30,33].…”
Section: Swimming Performance and Larval Conditionmentioning
confidence: 92%
“…Most swimming performance studies have focused on tropical coral reef fish larvae [14,[21][22][23][24][25], while those focusing on temperate species have only increased in recent years [19,[26][27][28][29][30][31]. Comparatively to fish larvae of tropical species, temperate fish larvae are considered to be weak swimmers, swimming at slower speeds than tropical species [23,28,32].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, analysing early‐life traits of D. sargus settlers in Marseilles (France) in 1994 and 1995, Vigliola (1998) find a mean PLD that is considerably higher than the one used in the present study (i.e., 28 vs. 16 days). Rossi et al (2019) observe even higher PLD with a mean of 40 ±5 days and ranging from 32 to 56 days in Corsica but explain this difference by the length of the fish at sampling (longer than 1 cm). In Spain, Macpherson and Raventos (2006) and Raventos et al (2021) find PLD ranging from 19 to 37 days (mean 27.6 ± 4.3 days) and from 14 to 32 days, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Endurance tests of raised gilthead seabream larvae of age 50 days showed that they could swim at a constant 12 cm s -1 speed during 42.2 ± 11.1 h, covering a mean distance of nearly 20 km (Faria et al, 2011). The critical swimming speed of larvae of ages 58 to 96 days collected at sea was recently estimated as 10.4 ± 1.7 cm s -1 (Rossi et al, 2019). The individuals collected here had similar ages and therefore probably also a significant capacity of movement, which they may have used to depart from drifting currents and swim to the coast and/or to remain close to the lagoon entrances, until they have developed sufficient ability to osmoregulate and sense lagoon waters.…”
Section: Discussionmentioning
confidence: 99%